Peran Pendidikan Agama Islam dalam Membangun Karakter Pemimpin - Alamsyah Kamil Waruwu; Azmi Prayogi; Fiqih Ahmad Alfisyahri (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2025)
This article discusses the strategic role of Islamic Religious Education (PAI) in shaping the character of leaders with integrity, justice, and responsibility. In the context of dynamic social change, leaders who have moral and spiritual foundations are an urgent need. This study uses a qualitative approach through a literature study of the latest academic sources. The results of the analysis show that the main values ​​in PAI—such as honesty, justice, responsibility, empathy, and sincerity—have a major contribution to the formation of leadership character. Effective implementation of PAI requires the integration of religious values ​​in leadership training, contextual learning, teacher role models, and active community participation. Obstacles such as the lack of understanding of the younger generation and the influence of the secular environment are challenges in themselves, but can be overcome with collaborative and contextually relevant educational strategies. This article emphasizes the importance of making PAI a foundation in building ethical and visionary leadership.